The Prophetic Pedagogy: Implementing Al-Ghazali’s Principles of Moral Psychology for Character Education in Islamic Schools - Isnaeni Marhani; Ahmad Musaddad; M. Makhtus Ali; Mustafa Hassan (Yayasan Adra Karima Hubbi, 2025)
This study examines the application of Al-Ghazali’s principles of moral psychology to contemporary character education within Islamic schools. The research is grounded in the concern that modern Islamic education often emphasizes cognitive and ritual learning while neglecting the cultivation of spiritual-ethical dispositions central to the prophetic educational tradition. Al-Ghazali’s framework, which integrates the purification of the heart, habit formation, and reflective self-discipline, provides a comprehensive moral psychology capable of strengthening holistic character development. The study aims to identify how Al-Ghazali’s concepts—such as tazkiyat al-nafs, disciplined habituation, and the alignment of knowledge with moral action—can be operationalized as pedagogical principles for classroom practice. The research adopts a qualitative design, using document analysis of Ihya’ ‘Ulum al-Din and Ayyuha al-Walad, thematic coding, and semi-structured interviews with Islamic education practitioners and curriculum developers in selected schools. The findings indicate that Al-Ghazali’s moral psychology can be translated into three core pedagogical domains: (1) emotional-spiritual formation through reflective and contemplative learning, (2) character habituation through structured routines and guided moral practice, and (3) moral reasoning development that connects knowledge to ethical decision-making. Schools that implement these principles demonstrate higher consistency between instructional content, teacher modeling, and student character outcomes. The study concludes that prophetic pedagogy grounded in Al-Ghazali’s moral insights offers a transformative framework for character education, bridging classical Islamic psychology with modern educational needs. The findings highlight the necessity of integrating spiritual affect, moral cognition, and ethical practice into a unified pedagogical model for Islamic schools.